2021
DOI: 10.3389/fpubh.2021.646780
|View full text |Cite
|
Sign up to set email alerts
|

Psychological Impact During the First Outbreak of COVID-19 on Frontline Health Care Workers in Shanghai

Abstract: Background: The COVID-19 pandemic is a significant health threat. Health care worker (HCWs) are at a significant risk of infection which may cause high levels of psychological distress. The aim of this study was to investigate the psychological impact of the COVID-19 on HCWs and factors which were associated with these stresses during the first outbreak in Shanghai.Methods: Between February 9 and 21, 2020, a total of 3,114 frontline HCWs from 26 hospitals in Shanghai completed an online survey. The questionnai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
15
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(16 citation statements)
references
References 41 publications
1
15
0
Order By: Relevance
“…The non-probabilistic sampling we used may somewhat hinder the validity of our findings, as has been reported in many published literatures during the early stage of the pandemic ( 26 , 35 , 36 ). However, our sample's prevalence of psychological distress was close to that of other studies conducted during the same period, indicating that our sample was somewhat representative of all HCWs in our hospital ( 12 ). In addition, the cross-sectional design led to a lack of causal relationships between variables.…”
Section: Limitationsupporting
confidence: 82%
See 3 more Smart Citations
“…The non-probabilistic sampling we used may somewhat hinder the validity of our findings, as has been reported in many published literatures during the early stage of the pandemic ( 26 , 35 , 36 ). However, our sample's prevalence of psychological distress was close to that of other studies conducted during the same period, indicating that our sample was somewhat representative of all HCWs in our hospital ( 12 ). In addition, the cross-sectional design led to a lack of causal relationships between variables.…”
Section: Limitationsupporting
confidence: 82%
“…A meta-analysis of studies conducted by April 17, 2020, found that the rate of depression and anxiety among HCWs in the pandemic was 23.2 and 22.8%, respectively ( 23 ). Notably, Feng et al applied the GHQ-12 to examine the mental health of staff from 26 hospitals in Shanghai between February 9 and 21, 2020, and found that the rate of psychological distress was 47.7% ( 12 ). Considering Changzhou is relatively near to Shanghai (200 km), and both studies were conducted during the early stages of the pandemic, the result of our study was similar to what was found in Shanghai.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Healthcare workers, a unique population who continued working during the COVID-19 state-ordered home isolation, with their frontline peers directly engaged in the clinical management of patients with COVID-19, are at high risk of mental morbidity (9)(10)(11) and negative health behaviors (12)(13)(14). A cross-sectional study consisting of 1,257 healthcare workers from China showed that females working in hospitals were predisposed to be psychologically stressed, with greater symptoms of anxiety, depression and distress than their male counterparts (15).…”
Section: Introductionmentioning
confidence: 99%